If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8 = 2(x + 12) Reorder the terms: 8 + 4x = 2(x + 12) Reorder the terms: 8 + 4x = 2(12 + x) 8 + 4x = (12 * 2 + x * 2) 8 + 4x = (24 + 2x) Solving 8 + 4x = 24 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + 4x + -2x = 24 + 2x + -2x Combine like terms: 4x + -2x = 2x 8 + 2x = 24 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + 2x = 24 + 0 8 + 2x = 24 Add '-8' to each side of the equation. 8 + -8 + 2x = 24 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 24 + -8 2x = 24 + -8 Combine like terms: 24 + -8 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 2y-3=11 | | 1x^2-6x=7 | | Y=14X+7 | | (x+3)(x+3)-(x-1)(x+5)(x+3)+(x-5)(x+5)3=0 | | 2x^2+16+28=0 | | -10x^11y^11Z^13+4x^11y^11z^13= | | 6c-14=-2 | | (-4y^8z^4)(-x^3y^3z^3)(x^8z^6)= | | 10x-126=4x-12 | | 102-4x=14x+16 | | 12x-28=56 | | 9a+5=13 | | r+10=3 | | 3x+11=-97-9x | | 192=0.5t | | 3x+11=23 | | 106-3x=3x+22 | | -5(-2x^4y^2z^2)(-x^3y^9Z^3)(x^4z^8)= | | r-6=-11 | | 95m+m=565 | | p-10=-20 | | 60t=45(t+2) | | r-3=-10 | | 4x^4+27x^2-81=0 | | [5y-1.3]=2.7 | | (-8x^2y^2z)(5xyz)= | | 136-2x=25x+19 | | n+10=4 | | 13-8x=65-22x | | -50-10x=8x+22 | | 3x^3(2x^5+10x^4-6)= | | -10n=100 |